Exploring international differences in ovarian cancer treatment: a comparison of clinical practice guidelines and patterns of care. Issue 11 (11th August 2020) - Norell, Charles H; Butler, John; Farrell, Rhonda; Altman, Alon; Bentley, James; Cabasag, Citadel J; Cohen, Paul A; Fegan, Scott; Fung-Kee-Fung, Michael; Gourley, Charlie; Hacker, Neville F; Hanna, Louise; et al.
Abstract : Introduction: The International Cancer Benchmarking Partnership demonstrated international differences in ovarian cancer survival, particularly for women aged 65–74 with advanced disease. These findings suggest differences in treatment could be contributing to survival disparities. Objective: To compare clinical practice guidelines and patterns of care across seven high-income countries. Methods: A comparison of guidelines was performed and validated by a clinical working group. To explore clinical practice, a patterns of care survey was developed. A questionnaire regarding management and potential health system-related barriers to providing treatment was emailed to gynecological specialists. Guideline and survey results were crudely compared with 3-year survival by 'distant' stage using Spearman's rho. Results: Twenty-seven guidelines were compared, and 119 clinicians completed the survey. Guideline-related measures varied between countries but did not correlate with survival internationally. Guidelines were consistent for surgical recommendations of either primary debulking surgery or neoadjuvant chemotherapy followed by interval debulking surgery with the aim of complete cytoreduction. Reported patterns of surgical care varied internationally, including for rates of primary versus interval debulking, extensive/'ultra-radical' surgery, and perceived barriers to optimal cytoreduction. Comparison showed that willingness to undertake extensive surgery correlated with survival across countries (rs =0.94, p=0.017). For systemic/radiation therapies, guideline differences were more pronounced, particularly for bevacizumab and PARP (poly (ADP-ribose) polymerase) inhibitors. Reported health system-related barriers also varied internationally and included a lack of adequate hospital staffing and treatment monitoring via local and national audits. Discussion: Findings suggest international variations in ovarian cancer treatment. Characteristics relating to countries with higher stage-specific survival included higher reported rates of primary surgery; willingness to undertake extensive/ultra-radical procedures; greater access to high-cost drugs; and auditing.